Quasi‐Additivity of the Radiative Effects of Marine Cloud Brightening and Stratospheric Sulfate Aerosol Injection - Boucher, Olivier; Kleinschmitt, Christoph; Myhre, Gunnar (Geophysical research letters, 2017)
Abstract Stratospheric sulfate aerosol injection (SAI) and marine cloud brightening (MCB) are the two most studied solar radiation management techniques. For the first time we combine them in a climate model to investigate their complementarity in terms of both instantaneous and effective radiative forcings. The effective radiative forcing induced by SAI is significantly stronger than its instantaneous counterpart evaluated at the top of atmosphere. Radiative kernel calculations indicate that this occurs because of a significant stratospheric warming and despite a large increase in stratospheric water vapor that strengthens the greenhouse effect. There is also a large decrease in high?level cloudiness induced by a stratification of the upper tropopause. Our model experiments also show that the radiative effects of SAI and MCB are quasi?additive and have fairly complementary patterns in the Tropics. This results in less spatial and temporal variability in the radiative forcing for combined SAI and MCB as compared to MCB alone.